Cyclotron motion without magnetic field - Hasdeo, Eddwi Hesky (2020)
Non-trivial Bloch band overlaps endow rich phenomena to a wide variety of quantum materials. The most prominent example is a transverse current in the absence of a magnetic field (i.e. the anomalous Hall effect). Here we show that, in addition to a dc Hall effect, anomalous Hall materials possess circulating currents and cyclotron motion without magnetic field. These are generated from the intricate wavefunction dynamics within the unit cell. Curiously, anomalous cyclotron motion exhibits an intrinsic decay in time (even in pristine materials) displaying a characteristic power law decay. This reveals an intrinsic dephasing similar to that of inhomogeneous broadening of spins. Circulating currents can manifest as the emission of circularly polarized light pulses in response to an incident linearly polarized (pulsed) electric field, and provide a direct means of interrogating a type of Zitterbewegung of quantum materials with broken time reversal symmetry.